Acral lymphomatoid papulosis: Report of five cases, differential diagnosis, and review. (13th January 2021) - Machan, Salma; Juárez Martín, África; Cullen Aravena, Daniella; Haro, Rosario; Pielasinski, Úrsula; Fuertes, Laura; Córdoba, Raúl; Santonja, Carlos; Rodríguez‐Pinilla, Socorro María; Requena, Luis
Abstract: Acral lymphomatoid papulosis (a‐LyP) is a rare clinical variant of LyP whose diagnosis may be challenging. A case series of a‐LyP was studied clinically, histopathologically, immunohistochemically, and from molecular point of view. Including ours, 25 cases of a‐LyP have so far been reported. Clinically, a‐LyP may present as acral involvement exclusively, in combination with mucosal lesions, (in itself a rare presentation), or in association with conventional LyP. The age of presentation was slightly higher than that of conventional LyP (55 vs 45 years) and a male predominance has been observed, as usually reported. Histopathologically, no morphological differences exclusively from conventional LyP were observed. LyP types A and E were the main variants. We describe for the first time one case of type D a‐LyP. Acral LyP is a rare entity and correct diagnosis can only be reached with clinical and histopathological correlation, to avoid aggressive treatment of this indolent lymphoproliferative disorder.